TAFSIR ILMI TENTANG PENCIPTAAN MANUSIA DALAM TAFSIR AL-JAWAHIR KARYA THANTHAWI JAWHARI - Muhammad Nasir; Asep Nana Sonjaya; Kerwanto (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
In response to this interpretation of science, there are two groups of scholars: opposers and supporters. In fact, many contemporary scholars are more moderate in responding to the interpretation of